Motives to Visit Urban Ecotourism Sites: A Study of a Botanical Garden in South Africa - HERMANN, Uwe P.; BOUWER, Samantha C. (Journal of Environmental Management and Tourism, 2023)
Botanical gardens are a global phenomenon. Historically developed with the intention of maintaining a living collection of plants (under scientific management) for the purpose of research and education, botanical gardens have evolved to provide an accessible urban alternative for ecotourism experiences. Given that many botanical gardens are publically funded, income secured from tourist visitation can help supplement (limited) government funds. The purpose of this study was determining the motives of visitors to a botanical garden in South Africa. Employing a quantitative methodology, an onsite intercept survey by means of convenience sampling yielded 304 usable responses. An exploratory factor analysis revealed six distinct visitor motivations. The results inform the marketing of botanical gardens with a view to promoting their financial sustainability as visitor attractions, and ultimately their continued role as centres of scientific research, conservation and education.